A Proposal of Applied Social Activities Module for Undergraduate Program of Turkish Language and Literature Teachers: A Qualitative Study - (:unkn) unknown (EDAM, 2011)
In this study, it was aimed to determine the views on the contributions provided for the prospective teachers with the course of Applied Social Activities suggested to be in the undergraduate program of the Turkish Language and Literature Teaching. A qualitative research method was used in order to evaluate the views of prospective teachers about contributions of a social activities course. The students of the 10th academic term at Marmara University Faculty of Ataturk Education Department of Secondary Social Sciences Education Turkish Language and Literature Teaching Undergraduate Program took part in this study. In spring semester of 2007-2008 academic year, the prospective teachers were asked to write their views about contributions provided by applications of social activities lesson. The data were obtained through these documents. The analysis of survey data ware carried out by induction analysis which is a method of content analysis. The results were sorted and analyzed according to content analysis. With respect to the findings obtained from the data, the prospective teachers evaluated the applications at two main categories as personal and occupational perspective. The collected data were interpreted by going through also related studies and a proposal made. As a result of the evaluation, the prospective teachers expressed that their skill of declamation in the face of community had developed, their social anxiety had decreased, their skills of cooperation and solidarity had developed, they had gained stronger self-confidence, their social skills had developed, their friends' and their own creativity had emerged, they had learned the situations that they can meet at phases of organization, they had gained experience on behalf of their career, they had got occupational material savings, and they had found the opportunity to apply theoretical knowledge. In the view of such information, practically (2-2-3) 4 hour Social Activities lesson was offered to prospective literature teachers at pre service period.
Keywords: Turkish Language and Literature Teacher Training; Undergraduate Program; Applied Social Activities; Higher Education